Determinação da unidade monitora para feixes de elétrons de uso clínico: comparação entre dois diferentes aceleradores lineares - Burin, Ana Laura [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
In radiotherapy, electron beams are commonly used for the treatment of superficial lesions, such as skin tumors and benign lesions such as keloids. Electrons are produced by clinical linear accelerator in teletherapy equipment. In order to accurately delivery the dose of radiation prescribed by the radiotherapy protocols, the medical physicist must determine the amount of radiation required to reach the target volume. This amount of radiation is expressed in monitor units (MU) of the linear accelerator. The calculation of MU depends on several radiometric parameters of the radiation fields as well as the characteristics of the target volume to be irradiated. In order to guarantee the quality of the treatment and the conformity of the radiation dose distribution, National Nuclear Energy Commission (CNEN) requires that the determined values of MU must be checked by an independent calculation. In this study 30 clinical cases were analyzed. For each clinical case it was determined the MU considering the treatment performed in two different linear accelerators. The MU values were calculated manually using the mathematical expression described by the literature and also using the spreadsheet elaborated in Excel Software and used in the routine of the HC-FMB Radiotherapy Service. In the manual calculations we considered the different radiometric parameters of the radiation fields of the two different accelerators. For a single linear accelerator, in the majority of cases analyzed, the maximum difference between the MU values calculated manually and those determined by the Excel spreadsheet was below 2.0%, results considered satisfactory by the radiotherapy quality control programs. Considering the treatment of the same clinical case being performed by the two different accelerators, the MU values may present significant differences due to the precision in determining the radiometric factors of the teletherapy beams. The use of the computational worksheet optimizes the time of the medical physicist and minimizes the errors in the calculation of the MU.

Na radioterapia, os feixes de elétrons são comumente utilizados para o tratamento de lesões superficiais, tais como tumores de pele e lesões benignas como os queloides. Os elétrons são produzidos em equipamentos de teleterapia do tipo acelerador linear clínico. As energias dos feixes de eletronterapia mais utilizadas variam entre 4,0 MeV a 20,0 MeV. Para a liberação precisa da dose de radiação preconizada pelos protocolos radioterápicos, o físico médico deve determinar a quantidade de radiação necessária que deve atingir o volume alvo. Esta quantidade de radiação é expressa em unidades monitoras (UM) do acelerador linear. O cálculo da UM depende de vários parâmetros radiométricos dos campos de radiação, bem como das características do volume alvo a ser irradiado. Para se garantir a qualidade do tratamento e a conformidade da distribuição da dose de radiação, a Comissão Nacional de Energia Nuclear (CNEN) exige que os valores determinados de UM sejam conferidos por um cálculo independente. Neste trabalho foram analisados 30 casos clínicos. Para cada caso clínico foi determinado a UM considerando o tratamento realizado em dois diferentes aceleradores linear. Os valores de UM foram calculados manualmente usando a expressão matemática da literatura e também utilizando a planilha de cálculo elaborada no Software Excel e utilizada na rotina do Serviço de Radioterapia do HC-FMB. Nos cálculos manuais considerou-se os diferentes parâmetros radiométricos dos campos de radiação dos dois distintos aceleradores. Para um mesmo acelerador linear, na maioria dos casos analisados, a diferença máxima entre os valores de UM calculados manualmente e os determinados pela planilha Excel ficou abaixo de 2,0%, resultados considerados satisfatórios pelos programas de controle de qualidade em radioterapia. Considerando o tratamento de um mesmo caso clínico sendo realizado pelos dois distintos aceleradores, os valores de UM podem apresentar diferenças significativas em virtude da precisão na determinação dos fatores radiométricos dos feixes de teleterapia. O uso da planilha computacional otimiza o tempo do físico médico e minimiza os erros no cálculo da UM
Keywords: Linear accelerator; Electron beam; Radiotherapy; Monitor unit; Acelerador linear; Feixes de elétron; Radioterapia; Unidade monitora